Dampak Pengaruh Sosial, Motivasi Pribadi Serta Literasi Keuangan untuk Menentukan Keputusan Investasi Generasi Milenial: Penelitian - Agus Putra Mardika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study explores the influence of social factors, personal motivation, and financial literacy on investment decisions of the millennial generation in Indonesia. Using a qualitative approach through literature studies, observations of 2020–2024 trends, and interviews with 12 millennial investors, it was found that family, friends, social media, and influencers play an important role in shaping investment behavior. Motivation for financial security and anxiety about economic uncertainty drive investment decisions. Digital financial literacy improves millennials' ability to manage finances and make investment decisions autonomously. The results show that despite being influenced by the social environment, millennials still prioritize autonomy in choosing investments according to personal goals. Strengthening financial literacy and social support are the keys to rational and confident investment decisions.